Reading Practices in Adult Education: Political Formation Contributions For High School Readers - ALVES, João Paulo da Conceição; PENHA, Ana Cláudia Figueiredo Martins (Faculdade de Filosofia e Ciências, 2018)
The research aimed toanalyse the relevance of reading practices in order to have a larger number of students that actually read more books on adult education.Corresponds a case study of a public school, in Macapá-AP. The data was collected qualitatively through semi-structured interviews with teachers of this modality. Analysing data was the technique used to interpreting the data itself. The results show that just a few teachers develop a variety of reading practices in the school,diversify the materials and its teaching methodology, they propose discussions for the students to expose their point of view,however it is fragile still when it comes to political aspects, due to the lack of: a bibliographic collection, reading habits and a short workload. Recebido em: 11/12/2016.Aprovado em: 02/04/2018.